2018
DOI: 10.3390/polym10020204
|View full text |Cite
|
Sign up to set email alerts
|

Neodymium Recovery by Chitosan/Iron(III) Hydroxide [ChiFer(III)] Sorbent Material: Batch and Column Systems

Abstract: A low cost composite material was synthesized for neodymium recovery from dilute aqueous solutions. The in-situ production of the composite containing chitosan and iron(III) hydroxide (ChiFer(III)) was improved and the results were compared with raw chitosan particles. The sorbent was characterized using Fourier transform infrared spectroscopy (FTIR) and scanning electron microscopy-energy dispersive X-ray analyses (SEM-EDX). The equilibrium studies were performed using firstly a batch system, and secondly a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 64 publications
3
38
1
1
Order By: Relevance
“…On the other hand, a higher residence time allows Cu(II) to diffuse and reach the active sites of the sorbent. The finding is in agreement with the results obtained by Demey et al on neodymium removal using the low cost composite material of chitosan/Iron(III) hydroxide [ChiFer(III)] [46], who conclude that the external film diffusion reduced under the higher superficial velocity, thus, resulting in a faster breakthrough. The Cu(II) adsorption capacity was 59.65, 84.98 and 98.16 mg/kg with the increasing residence times for 8, 10 and 12 min, respectively.…”
Section: The Effect Of Residence Time On Cu(ii) Removalsupporting
confidence: 92%
See 1 more Smart Citation
“…On the other hand, a higher residence time allows Cu(II) to diffuse and reach the active sites of the sorbent. The finding is in agreement with the results obtained by Demey et al on neodymium removal using the low cost composite material of chitosan/Iron(III) hydroxide [ChiFer(III)] [46], who conclude that the external film diffusion reduced under the higher superficial velocity, thus, resulting in a faster breakthrough. The Cu(II) adsorption capacity was 59.65, 84.98 and 98.16 mg/kg with the increasing residence times for 8, 10 and 12 min, respectively.…”
Section: The Effect Of Residence Time On Cu(ii) Removalsupporting
confidence: 92%
“…This may be due to the fact that the adsorption is particularly active in the dilute concentrations. Demey et al and Kleinübing et al also observed a higher sorption capacity obtained from the batch experiment than from the column experiments [46,47]. The fact was explained by the resistance to the film diffusion active in the low concentrations which are similar to the present study.…”
Section: The Effect Of Inlet Concentration On Cu(ii) Removalsupporting
confidence: 89%
“…The creation of biofilms and the formation of manganese oxide coatings on the surface of chalcedonite causes the deposit to work continuously (does not run out). For that very reason, the Thomas model commonly applied to describe the continuous column system [30] may not be used.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Using a continuous sorption system allows a better approach to real industrial applications. A few models that can describe these processes have been reported in the literature [22,30]. However, only a limited number of references exist on the modelling of the combined and simultaneous removal of the above pollutants [6,9].…”
mentioning
confidence: 99%
“…The developing of cheap and easy-to-operate wastewater treatment methods are crucial in order to surpass the low economies issues and maintain the sanitation. Among the most used methods to wastewater treatment are biological processes, as they are economically viable compared to other processes such as advanced oxidation or precipitation [2][3][4][5][6]i.e. vehicle operating costs and speeds are also allowed to vary over time.…”
Section: Introductionmentioning
confidence: 99%